440 Impacts of Ergot Alkaloid Exposure During Mid and Late Gestation on Maternal Glucose, Insulin, and NEFA Concentrations and the Effects on Offspring Birth Weight. (7th December 2018) - Greene, M; Britt, J; Miller, M; Adams, S; Duckett, S
Abstract: The objective of this study was to evaluate glucose, insulin, and NEFA concentrations in gestating ewes consuming ergot alkaloids from endophyte-infected tall fescue seed at two stages of gestation and the effects on offspring birth weight. Suffolk ewes (n = 60; 83kg) estimated to be carrying twins at d35 of gestation were randomly assigned to endophyte-free tall fescue seed (E-; 0.0µg ergovaline + ergovalinine/g) or endophyte-infected tall fescue seed (E+; 4.14µg ergovaline + ergovalinine/g) during two stages of gestation (MID: d35 – d85 and LATE: d86 – parturition) creating 4 treatments: E- MID and LATE (E-/E-), E- MID and E+ LATE (E-/E+), E+ MID and E- LATE (E+/E-), and E+ MID and LATE (E+/E+). A subsample of ewes (n=26), representative of all 4 treatments was used for blood hormone analysis. Blood samples were collected from ewes at d35, 55, 85, 105, and 133 of gestation. Glucose, insulin, and NEFA levels were analyzed using colormetric assays, ELISAs, and spectrophotometric assays respectively. During gestation, insulin values were not different (P>0.05) by treatment. Significant interactions between treatment and gestational age were found for glucose and glucose-insulin ratios (P<0.01, P<0.05). Glucose concentrations for E-/E+ ewes were higher compared to E-/E- ewes at d133; whereas glucose-insulin ratios were higher for E+/E+ ewes at d55, E-/E+ ewes at d105, and E+/E- ewes at d133 compared to E-/E- ewes. NEFA concentrations differed by treatment (P<0.01), with E+/E- ewes having higher NEFA levels when compared to all other treatments. At birth, lamb weight was reduced (P<0.01) in ewes fed E+ seed during LATE gestation. A significant correlation (P<0.01, r=0.59) was found between lamb birth weight and d133 maternal NEFA concentrations. Introducing ergot alkaloids during MID and LATE gestation influences glucose and NEFA concentrations, which may alter lamb birth weight.